2001
DOI: 10.1034/j.1399-0004.2001.600301.x
|View full text |Cite
|
Sign up to set email alerts
|

Distal limb malformations: underlying mechanisms and clinical associations

Abstract: Congenital malformations of the extremities are conspicuous and have been described through the ages. Over the past decade, a wealth of knowledge has been generated regarding the genetic regulation of limb development and the underlying molecular mechanisms. Recent studies have identified several of the signaling molecules, growth factors, and transcriptional regulators involved in the initiation and maintenance of the apical ectodermal ridge (AER) as well as the molecular markers defining the three axes of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 74 publications
0
18
0
1
Order By: Relevance
“…However, since approximately 30% SHFM1 obligate carriers show no phenotypic abnormalities (Scherer et al, 1994a), it has been suggested that other alleles and/or genetic mechanisms might be involved in the origin of the human lesion (Genuardi et al, 1993). Furthermore, variable expressivity, segregation distortion, locus heterogeneity, and syndromic association with other anomalies have so far prevented the identification of the SHFM1 gene(s) (Sifakis et al, 2001;Zlogotora, 1994;Palmer et al, 1994). None of the candidate genes located on 7q21.3 is directly interrupted by any of the deletions, inversions, or translocations on 7q21 associated with the disease (Crackower et al, 1996).…”
mentioning
confidence: 96%
“…However, since approximately 30% SHFM1 obligate carriers show no phenotypic abnormalities (Scherer et al, 1994a), it has been suggested that other alleles and/or genetic mechanisms might be involved in the origin of the human lesion (Genuardi et al, 1993). Furthermore, variable expressivity, segregation distortion, locus heterogeneity, and syndromic association with other anomalies have so far prevented the identification of the SHFM1 gene(s) (Sifakis et al, 2001;Zlogotora, 1994;Palmer et al, 1994). None of the candidate genes located on 7q21.3 is directly interrupted by any of the deletions, inversions, or translocations on 7q21 associated with the disease (Crackower et al, 1996).…”
mentioning
confidence: 96%
“…Notably, this locus in humans was known to be syntenic to the locus in mice causing the Dactylaplasia (Dac) phenotype, which comprises absence of the central digits with clefts or monodactyly and thus closely resembles human SHFM. The gene in this region now known as FBXW4 emerged as a candidate gene for human SHFM at this locus [Ianakiev et al, 1999;Sifakis et al, 2001]. Failure to identify mutations through PCR-based strategies led to the identification of rearrangements affecting the SHFM3 region in multiple linked families [de Mollerat et al, 2003].…”
Section: Recurrent Genomic Duplicationsmentioning
confidence: 99%
“…Studies in mice have revealed that p63 is important in ectodermal development and keratinocyte differentiation De Laurenzi et al, 2000). In humans, p63 mutations have been associated with five autosomal dominant inherited syndromes, that is, EEC, AEC, ADULT, limb-mammary syndrome, and nonsyndromic split hand/foot malformation (Celli et al, 1999;Sifakis et al, 2001;Brunner et al, 2002). The p73 knockout mouse has chronic infections and defects in neural development and pheromone function .…”
Section: Introductionmentioning
confidence: 99%